Efektivitas Layanan Informasi Menggunakan Media Animasi Meningkatkan Sikap Anti Bullying Peserta Didik - Mirnayenti, Mirnayenti; Syahniar, Syahniar; Alizamar, Alizamar (Universitas Negeri Padang, 2015)
Individual attitudes can occur because of social interaction. Some learners anyone dared to oppose, silent and engaged in acts of bullying, so that the necessary efforts to improve anti-bullying stance. The attitude of the students towards bullying that can be seen in the journal cases BK teacher / school counselor. One of the efforts made in improving the anti bullying learners with information services. This study aimed to test the effectiveness of media information services using animation to enhance the anti-bullying attitudes of learners. This study uses quantitative methods. This research is a Quasi Experiment with pretest-posttest control group design. The study population was students of SMPN 13 Padang as EG and SMP 12 Padang as CG and samples selected using purposive sampling technique. The research instrument used Likert Scale models, then analyzed using the t-test with SPSS version 17. The findings of this study are: (1) there is a significant difference between anti bullying learners EG before and after following the service information using animation media, (2) there is a difference between the attitude of anti-bullying learners KK before and after following the service information without the use of animation media , (3) there is a difference in attitude differences anti bullying learners CG given treatment information services using animation media, with families given treatment information services without the use of animation media. Based on the above findings, we can conclude that the service information using animation media effectively improve anti-bullying attitudes of learners.Â